Tax reforms and their varying impacts on private households in Germany: Socio-economic modelling opportunities in a macro-econometric input-output model - Thomas Drosdowski; Britta Stöver (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2016)
Taxation of incomes generated by economic agents is a main pillar of redistributive social policies undertaken by the government in Germany. The apparent lack of sufficient adjustments of the tax schedule during the period 2005-2015 has led to higher average annual growth rates in taxes than in income. This development has triggered a public dispute about alleged bracket creep, i.e. inflationary-caused nominal income increase pushing taxable income into higher tax bracket, which apparently poses higher tax burden especially among households with small and medium incomes. The aim of this paper is an analysis of the effects of a permanent proportional income tax reduction on the total economy as well as on the income situation of different household types, against the background of repeated public demands for tax reliefs resulting from increased tax burdens in recent years. The taxation scenario is not calculated on a microeconomic level but uses a macro-econometric approach instead, in order to give a broad overview over a wide variety of effects. By combining the macro-econometric input-output model INFORGE with the socio-economic system DEMOS containing household-specific income and consumption information we can assess how a simple fiscal measure would affect the economy, different household types, and inequality. It can be shown that a tax reduction has a positive aggregate effect throughout the economy in all years of the tax reform. Working households with high incomes profit most from simple tax cuts. Non-working households, however, are faced with comparably smaller positive deviations in income, which exacerbates the projected distance between household incomes and contributes to further increasing inequality.
Keywords: E27; E62; E64; H2; 330; taxation; scenario analysis; economic effects; inequality; private households